Landscape and Paleoclimatic influences on the genetic population structure of four forest-dependent passerines in the Eastern Cape of South Africa - Mulvaney, Jake Matthew (Stellenbosch : Stellenbosch University, 2021)
Thesis (PhD)--Stellenbosch University, 2021.